Networks of Contextualized Data: A Framework for Cyberinfrastructure Data Management. - CARTER, PAMELA E.; GREEN, GINA (Communications of the ACM, 2009)
The article discusses data management activities in the context of networked information technologies. A definition is given of cyberinfrastructure as an overarching concept encompassing items such as hardware, software, and the personnel that are the underlying foundation that supports collaborative network activities. Other topics include information as contextualized data, the management of information systems (IS) in different cultures and locations, and the importance of contextualized data networks and cyberinfrastructure data management in a collaborative environment.